EXPLORING BOUNDARIES: A PYSCHOLINGUISTICS COMPARISON BETWEEN HUMAN LANGUAGE AND NON-HUMAN COMMUNICATION - Silalahi, Ariel Jonivedi; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
Language is the most effective and important communication tool in social life. Language has a high value in human life in everyday communication. However, as living creatures, humans and animals have a communication system between humans and animals. This language ability is what distinguishes humans from animals. Humans organize their lives with language. While animals also have their own way of organizing their lives, especially in communicating. This study aims to analyze the differences between how humans and animals communicate. By using the literature review method as the basis for collecting information, this study seeks to understand the main differences in communication systems and language abilities between the two. The results of the analysis show that the fundamental differences between human and animal communication lie in the structure of the communication system and the language abilities they possess.